2016
DOI: 10.14746/10.14746/eip.2016.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognitive Domain Coordination in Left-Behind Children: A Comparative Study of Left-Behind and Non-Left-Behind Children in Rural China

Abstract: Forty-seven left-behind children (LB) and 40 non-left-behind children (NL) in rural China were interviewed to evaluate moral, conventional, and personal violations by providing judgments and justifications. The results suggested that both LBs and NLs differentiate the rules of moral, conventional and personal domains. However, there are some differences: 1. The NL considered it acceptable to commit a personal infraction when there was no rue prohibiting it, while the LB considered it wrong; 2. The younger male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In addition to gender, changes in year may also moderate the relationship between CT and PIU. Previous study has found that the correlation between CT and PIU decreases by growing years (Hsieh et al, 2021), However, other studies have shown that the correlation between CT and PIU increases with increasing years (Zhang et al, 2012;Wei, 2014;Liu, 2016;Li, 2020). Therefore, this study would explore the differences in CT and PIU among students in different years.…”
Section: Survey's Yearmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition to gender, changes in year may also moderate the relationship between CT and PIU. Previous study has found that the correlation between CT and PIU decreases by growing years (Hsieh et al, 2021), However, other studies have shown that the correlation between CT and PIU increases with increasing years (Zhang et al, 2012;Wei, 2014;Liu, 2016;Li, 2020). Therefore, this study would explore the differences in CT and PIU among students in different years.…”
Section: Survey's Yearmentioning
confidence: 94%
“…Some studies have found that there is a low positive correlation between CT and PIU of subjects in journal papers (Zhang et al, 2012), but there is also a moderate positive correlation between CT and PIU of subjects in journal papers (Yang et al, 2017). In the master's thesis and doctoral dissertation, some studies found that there was a low degree of positive correlation between CT and PIU (Wei, 2014), but other studies found that there was a moderate degree of positive correlation between CT and PIU (Liu, 2016). Therefore, this study would investigate the moderating effect in journal papers and dissertation on CT and PIU.…”
Section: Source Of Publicationmentioning
confidence: 97%
See 1 more Smart Citation